2014
DOI: 10.1186/1471-2407-14-334
|View full text |Cite
|
Sign up to set email alerts
|

Use of NQO1 status as a selective biomarker for oesophageal squamous cell carcinomas with greater sensitivity to 17-AAG

Abstract: BackgroundOesophageal squamous cell carcinoma (OSCC) is a major health burden in Sub-Saharan Africa, and novel chemotherapies are urgently required to combat this disease. The heat shock protein 90 (HSP90) inhibitor 17-N-allylamino-17-demethoxygeldanamycin (17-AAG) has previously been proposed as a possible candidate drug. NADPH quinone oxidoreductase 1 (NQO1) is known to increase the potency of 17-AAG, therefore we investigated the effects of 17-AAG in OSCC cell lines in the context of their NQO1 status.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Thus, the mechanisms of acquired resistance to these drugs may be similar. NQO1 is a homodimeric metabolic enzyme that catalyzes the conversion of quinones to hydroquinones and has an important role in sensitivity to 17-AAG [ 29 , 21 ]. Loss or low activity of NQO1, by the reduction of its mRNA or the emergence of inactivating polymorphisms in the NQO1 gene, leads to resistance to 17-AAG in pancreatic cancer cells and glioblastoma cell lines [ 30 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mechanisms of acquired resistance to these drugs may be similar. NQO1 is a homodimeric metabolic enzyme that catalyzes the conversion of quinones to hydroquinones and has an important role in sensitivity to 17-AAG [ 29 , 21 ]. Loss or low activity of NQO1, by the reduction of its mRNA or the emergence of inactivating polymorphisms in the NQO1 gene, leads to resistance to 17-AAG in pancreatic cancer cells and glioblastoma cell lines [ 30 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In S4 Table , many genes used by QRFs are pointed out to be related with cancers in literatures. For example, the inhibition activity of 17-AAG can be increased by the expression of NQO1 [ 23 ]. Also, the mutation of BRAF is predicted as a drug efficacy marker for some MEK inhibitors, including AZD6244, PD-0325901 and PLX4720 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kung et al demonstrated that β-Lapachone-induced cytotoxicity of three different lung cancer cell lines was positively correlated with NQO1 expression and enzyme activity [ 37 ]. Hadley et al suggested that stratification of patients on the basis of NQO1 protein levels could identify a subset of esophageal squamous cell carcinomas patients that may potentially benefit from administration of low doses of 17-AAG, possibly in combination with other chemotherapeutics [ 38 ]. Huang et al reported that the potency and NQO1-dependent therapeutic window of deoxynyboquinone and its apparent reduced metabolism by one-electron oxidoreductases make this drug (or derivatives) very promising [ 39 ].…”
Section: Discussionmentioning
confidence: 99%